The assessment of drawings of 5 grade students in the state or private schools, according to the different variables - DOĞAN, PESENT (ELSEVIER SCIENCE BV, 2015)
Art education is a field of education which is given importance and regularly conducted throughout the contemporary and civilized world. At present, in the education of students of different age groups in every civilized country, capability development studies are conducted as drawing studies and it is an important subject. It is known that visual art education in public and private schools in our country will have a significant influence on the careers of students in their future lives. The objective of this study was to evaluate the creative ideas of 5th graders who had visual art lessons using the same programs in public and private schools in 2013 - 2014 academic year and the evaluation was performed according to different variables. This study was performed on 20 students from public schools and on 20 students from private schools and their studies in art education classes were evaluated with respect to their use of materials, techniques, themes and creative approaches, and the results were interpreted by means of qualitative research. by (C) 2015 Published by Elsevier Ltd.
Keywords: Visual Arts Education; Creative Thinking; Teaching Methods